2014
DOI: 10.1371/journal.ppat.1004052
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction between Glutathione and the Capsid Is Required for the Morphogenesis of C-Cluster Enteroviruses

Abstract: Glutathione (GSH) is the most abundant cellular thiol playing an essential role in preserving a reduced cellular environment. Cellular GSH levels can be efficiently reduced by the GSH biosynthesis inhibitor, L-buthionine sulfoximine (BSO). The aim of our study was to determine the role of GSH in the growth of two C-cluster enteroviruses, poliovirus type 1 (PV1) and coxsackievirus A20 (CAV20). Our results show that the growth of both PV1 and CAV20 is strongly inhibited by BSO and can be partially reversed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 41 publications
3
39
1
Order By: Relevance
“…The addition of 1 to 3 mM guanidine hydrochloride (GnHCl) at midinfection, which inhibits RNA synthesis, caused the accumulation of procapsids, which could be chased into virus particles (57,58). From our studies with BSO, we found that 75S particles, although they are made in normal amounts during infection in GSH-depleted cells, do not progress into forming mature virus, an observation which suggests that 75S may not be a functional capsid intermediate (22).…”
Section: Formation Of 75s Empty Capsids: [(Vp0 Vp1 Vp3) 5 ] 12mentioning
confidence: 86%
See 3 more Smart Citations
“…The addition of 1 to 3 mM guanidine hydrochloride (GnHCl) at midinfection, which inhibits RNA synthesis, caused the accumulation of procapsids, which could be chased into virus particles (57,58). From our studies with BSO, we found that 75S particles, although they are made in normal amounts during infection in GSH-depleted cells, do not progress into forming mature virus, an observation which suggests that 75S may not be a functional capsid intermediate (22).…”
Section: Formation Of 75s Empty Capsids: [(Vp0 Vp1 Vp3) 5 ] 12mentioning
confidence: 86%
“…Using BSO, the inhibitor of poliovirus morphogenesis, we observed that GSH depletion leads to the accumulation of "provirion-like" particles, which migrate slightly faster on sucrose gradients than the 150S particles made under normal growth conditions and contain essentially no infectious virions, suggesting that GSH is required for the final maturation of viral particles (22).…”
Section: The Provirion: [(Vp0 Vp1 Vp3) 5 ] 12 Rnamentioning
confidence: 96%
See 2 more Smart Citations
“…Capsid binder Pirodavir [5], Pleconaril b [5], Pocapavir (V-073) b [5], Vapendavir (BTA798) b [ Buthionine sulfoximine (BSO) [46 ], TP219 [47 ] replication have been discovered, spurring host-directed drug development. Since some host factors appear to be used by many -or even all -enteroviruses, inhibitors of these cellular factors may have broad-spectrum activity.…”
Section: Type Of Inhibitor Compoundsmentioning
confidence: 99%